2013
DOI: 10.1080/02699931.2012.689758
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation characteristics and cognitive vulnerabilities interact to predict depressive symptoms in individuals at risk for bipolar disorder: A prospective behavioural high-risk study

Abstract: Recent work has identified Behavioral Approach System (BAS) sensitivity as a risk factor for the first onset and recurrence of mood episodes in bipolar disorder, but little work has evaluated risk factors for depression in individuals at risk for, but without a history of, bipolar disorder. The present study evaluated cognitive styles and the emotion-regulatory characteristics of emotional clarity and ruminative brooding as prospective predictors of depressive symptoms in individuals with high versus moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 93 publications
3
29
1
Order By: Relevance
“…Although the heightened difficulty in accepting emotions in this cohort contradicts previous findings in which emotional acceptance (as measured by the Cognitive Emotion Regulation Questionnaire) in BD was no different to controls, the general pattern of results is consistent with broader research findings in which cognitive-change related emotion regulation has been demonstrated as being impaired in BD (Green et al, 2007(Green et al, , 2011Gruber et al, 2011Gruber et al, , 2012Townsend and Altshuler, 2012;Rowland et al, 2013a). Importantly, these present results also sit well in the context of a study that showed that emotional clarity buffered against the exacerbating effects of negative cognitive styles on depressive symptoms in a group at high risk for BD (Stange et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although the heightened difficulty in accepting emotions in this cohort contradicts previous findings in which emotional acceptance (as measured by the Cognitive Emotion Regulation Questionnaire) in BD was no different to controls, the general pattern of results is consistent with broader research findings in which cognitive-change related emotion regulation has been demonstrated as being impaired in BD (Green et al, 2007(Green et al, , 2011Gruber et al, 2011Gruber et al, , 2012Townsend and Altshuler, 2012;Rowland et al, 2013a). Importantly, these present results also sit well in the context of a study that showed that emotional clarity buffered against the exacerbating effects of negative cognitive styles on depressive symptoms in a group at high risk for BD (Stange et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Although its aetiology remains unclear, difficulties in emotion regulation are becoming increasingly recognised in models of BD pathophysiology, particularly as mood lability and emotional regulation difficulties may contribute negatively to functional outcomes (Meyer et al, 2001; e.g., Green et al, 2007;Gruber et al, 2012;Townsend and Altshuler, 2012;Stange et al, 2013;Strejilevich et al, 2013;Rossell, 2014e, 2014d).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current findings are in line with a study of Crues et al (2002) who observed that the improvement in cognitive coping strategies and reduction in dysfunctional attitudes were closely associated with decreases in depressive symptoms in HIV-infected men. Moreover, a recent study of Stange et al (2013) observed in adolescents at risk for bipolar disorder that emotion-regulatory characteristics and cognitive styles may work in conjunction to confer risk for and resilience against future depression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ability to identify complex emotions generally improves during adolescence (Burnett, Bird, Moll, Frith, & Blakemore 2009), some children and adolescents possess deficits in emotional clarity that increase the risk of depressive symptoms (Flynn & Rudolph, 2010, 2014; Resurreccion, Salguero, & Ruiz-Aranda, 2014; Stange, Alloy, Flynn, & Abramson, 2013a; Stange et al, 2013b). Recent research also indicates that deficits in emotional clarity may impair one’s ability to adaptively respond to stressful life events (Ramos, Fernandez-Berrocal, & Extremera, 2007), including perceived peer victimization (Flynn & Rudolph, 2010, 2014).…”
Section: Introductionmentioning
confidence: 99%